1976
DOI: 10.1159/000119620
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus Secondary to Intracranial Hemorrhage in Premature Infants

Abstract: Premature (low birth weight) infants are particularly susceptible to intracranial hemorrhage. This frequently arises from the subependymal area and may dissect into the brain or into the ventricles. If the infant survives, hydrocephalus is a frequent sequela. Because of major improvements in the care of premature infants in recent years and the proliferation of intensive care nurseries, increasing numbers of low birth weight infants are surviving and developing hydrocephalus. Seven cases are described of infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…7,14 There are case reports of shunt failure attributed to high protein levels. 10,15,28 Taylor and Peter 24 recommended delaying shunt insertion in patients with PHH and low birth weight. They speculated that inserting a shunt prior to Day 35 of life has a higher risk of failure that "probably correlates with a high concentration of blood breakdown products in the cerebrospinal fluid during the first month after intra-ventricular hemorrhage."…”
Section: Discussionmentioning
confidence: 99%
“…7,14 There are case reports of shunt failure attributed to high protein levels. 10,15,28 Taylor and Peter 24 recommended delaying shunt insertion in patients with PHH and low birth weight. They speculated that inserting a shunt prior to Day 35 of life has a higher risk of failure that "probably correlates with a high concentration of blood breakdown products in the cerebrospinal fluid during the first month after intra-ventricular hemorrhage."…”
Section: Discussionmentioning
confidence: 99%
“…The surgical treatment of PHH has usually consisted of performing a shunt procedure several days or weeks after diagnosis, usually when the infants were 6 weeks to 6 months of age [2,9,19], The considerable delay while waiting for the bloody CSF to clear was based on the hope that the fluid would be less viscid, thus preventing obstruction. Despite such pre cautions.…”
Section: Resultsmentioning
confidence: 99%
“…In Lorber and Bhat'% [9] large series, obstruction occurred in 46% of patients, two-thirds of whom required more than one shunt revision. Wise and Bal lard [19] treated 7 infants; 3 of these infants needed multiple shunt revisions because of obstruction.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, intermittent reduction of CSF volume via a ventricular catheter reservoir (VCR) has become an accepted alter native or adjunct to the above therapies. Introduced in 1975 by Deonna et al [20] and later reported by Wise and Ballard [21], VCRs quickly became a safe and reasonable means by which cortical mantle thickness could be preserved while the elevated protein and cell counts in posthemorrhagic CSF became favorable for shunting. McComb et al [22] and Gaskill et al [23] have reported 20 and 38 infants, respectively, treated initially for PHH with a combination of serial LPs and VCRs.…”
Section: Introductionmentioning
confidence: 99%